2006
DOI: 10.1073/pnas.0606271103
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of carcinogenesis with and without a mutator mutation

Abstract: Carcinogenesis involves the acquisition of multiple genetic changes altering various cellular phenotypes. These changes occur within the fixed time period of a human lifespan, and mechanisms that accelerate this process are more likely to result in clinical cancers. Mutator mutations decrease genome stability and, hence, accelerate the accumulation of random mutations, including those in oncogenes and tumor suppressor genes. However, if the mutator mutation is not in itself oncogenic, acquiring that mutation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 34 publications
5
107
0
1
Order By: Relevance
“…Multiple studies showed that continuous formation of DNA double-strand breaks might contribute to increased genomic instability, leading to tumorigenesis, because of breach of a barrier (such as DNA damage response including p53 activation). (3,4,25,26) In this study, IHC staining of c-H2AX protein was carried out to detect presence of DNA damage in the tumor tissues and c-H2AX expression was observed in 38 of 84 samples (45.2%; Table 1). Interestingly, our result showed that increased expression of Wip1 was significantly associated with c-H2AX expression (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies showed that continuous formation of DNA double-strand breaks might contribute to increased genomic instability, leading to tumorigenesis, because of breach of a barrier (such as DNA damage response including p53 activation). (3,4,25,26) In this study, IHC staining of c-H2AX protein was carried out to detect presence of DNA damage in the tumor tissues and c-H2AX expression was observed in 38 of 84 samples (45.2%; Table 1). Interestingly, our result showed that increased expression of Wip1 was significantly associated with c-H2AX expression (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…What the correlation does suggest, is that therapy will be a strong selection pressure, and that genetically heterogeneous tumours have better chances of getting through it. In any case, different strands of evidence suggest that the instability of cancer cells helps rather than hampers their evolution (see also Beckman and Loeb 2006). Although it is still unclear whether fidelity of heredity is ideal for evolution, we can safely consider it within the required range.…”
Section: Abundance Of Variation (V) and Fidelity Of Heredity (H)mentioning
confidence: 99%
“…Hence natural selection was proposed to account for this: if the first hit is already advantageous for the cell, it will be spread through the population, making the combination of hits more likely by changing the background conditions on which the next hit will arise 16 . A related -and still very much debated -hypothesis is that of the "mutator phenotype" (Beckman and Loeb 2006;Loeb 1991), according to which one of the first hits increases genetic instability and thereby makes subsequent hits more likely. Once more, however, the CSC model provides an alternative explanation which is equally convincing: if cancer either arises in a stem cell or revert the cell to a pre-wired stem-cell state, the cell has the necessary lifespan.…”
Section: Resistance To Therapymentioning
confidence: 99%
“…Mathematical models using the focused quantitative modeling methodology (5) have demonstrated that genetic instability enhances the efficiency of carcinogenesis, a result that is robust across all plausible parameter values and model types (5)(6)(7). More efficient mechanisms of carcinogenesis should be more common in clinical tumors.…”
mentioning
confidence: 99%